Extremists take advantage of the political vacuum in Kosovo - Dušan Reljić (Stiftung Wissenschaft und Politik (SWP), 2003)
The death of two Serb youths killed by machine-gun fire from unidentified assailants while on a bathing trip not far from the village of Goraždevac near Peć on 13 August 2003 (four further youths were seriously injured in the incident) marks the start of an even more brutal episode in the battle for Kosovo. The European Union and the USA need to respond promptly by stepping up their efforts to achieve a sustainable peace accord for the region. Otherwise, a political vacuum could build up, creating new opportunities for extremist forces. (SWP Comments / SWP)
Keywords: 320